Ottomans Imagining Japan - Worringer, R. author. aut Link
XVIII, 350 p.
Keywords: Today's "clash of civilizations" between the Islamic world and the West are in many ways rooted in 19th-century resistance to Western hegemony. This compellingly argued and carefully researched transnational study details the ways in which Japan served as a model for Ottomans in attaining "non-Western" modernity in a Western-dominated global order.